A new copper(II) supramolecular coordination polymer and a dinuclear compound with multifunctional 2‐amino‐5‐sulfobenzoic acid and flexible N‐donor ligands: synthesis, structure and characterization. Issue 3 (21st February 2018) - Li, Peng-Cheng; Zhang, Kou-Lin
Abstract : A new Cu II supramolecular coordination polymer and an asymmetric dinuclear compound have been synthesized from multifunctional 2‐amino‐5‐sulfobenzoic acid and flexible N‐donor ligands and their structures have been determined. Abstract : Multifunctional 2‐amino‐5‐sulfobenzoic acid (H2 afsb) can exhibit a variety of roles during the construction of supramolecular coordination polymers. The pendant carboxylic acid, sulfonic acid and amino groups could not only play a role in directing bonding but could also have the potential to act as hydrogen‐bond donors and acceptors, resulting in extended high‐dimensional supramolecular networks. Two new Cu II coordination compounds, namely catena ‐poly[[[diaquacopper(II)]‐μ‐1, 6‐bis(1 H ‐1, 2, 4‐triazol‐1‐yl)hexane‐κ 2 N 4 : N 4′ ] bis(3‐amino‐4‐carboxybenzenesulfonate) dihydrate], [Cu(C10 H16 N6 )2 (H2 O)2 ](C7 H6 NO5 S)2 ·2H2 O n or [Cu(bth)2 (H2 O)2 ](Hafsb)2 ·2H2 O n, (1), and bis(μ‐2‐amino‐5‐sulfonatobenzoato‐κ 2 O 1 : O 1′ )bisμ‐1, 2‐bis[(1 H ‐imidazol‐1‐yl)methyl]benzene‐κ 2 N 3 : N 3′ bis[aquacopper(II)] trihydrate, [Cu2 (C7 H5 NO5 S)2 (C14 H14 N4 )2 (H2 O)2 ]·3H2 O or [Cu2 (afsb)2 (obix)2 (H2 O)2 ]·3H2 O, (2), have been obtained through the assembly between H2 afsb and the Cu II ion in the presence of the flexible N‐donor ligands 1, 6‐bis(1 H ‐1, 2, 4‐triazol‐1‐yl)hexane (bth) and 1, 2‐bis[(1 H ‐1, 2, 4‐triazol‐1‐yl)methyl]benzene (obix), respectively. Compound (1) consists of a cationic coordination polymeric chain and 3‐amino‐4‐carboxybenzenesulfonate (Hafsb − ) anions. Compound (2) exhibits an asymmetric dinuclear structure. There are hydrogen‐bonded networks within the lattices of (1) and (2). Interestingly, both (1) and (2) exhibit reversible dehydration–rehydration behaviour.